KETERLIBATAN ANAK MUDA KOTA BEKASI DALAM KEBIJAKAN SMART CITY - Elvira Suryani (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Smart City is a big issue in the world and Indonesia that focuses on the involvement of the active roleof the community in city development using a centric approach. This is done by the government to beone of the solutions to solve various problems that occur in urban areas. The concept of Smart City hasbeen implemented in several major cities in Indonesia such as Jakarta, Bandung, Surabaya, and Bekasione of them. The background of this research is based on the concept of a Smart City which is also inline with the vision and mission of Bekasi City, namely to "Realize Bekasi Advanced, Prosperous andIkhsan". The purpose of this study is to find out the opinions of young people in Bekasi City towardsSmart City policies. In addition, this study is also to find out information about the participation ofBekasi City youth in Smart City policies. By using qualitative research methods and descriptive dataanalysis, it can be found that the involvement of Bekasi City youth in the Smart City Policy is stillspontaneous. However, it has not been fully aware of the Smart City policy in Bekasi City. Therefore,encouragement from the government is needed to provide an understanding of the presence of smartcities in Bekasi City.